Mental health and aging in New Zealand: mixed-methods analysis of experiences of healthcare from a survey of older adults with mental health conditions - Debbie Peterson; Fiona Imlach; Ruth Cunningham (Kōtuitui)
Little is known about the experiences of older people who seek mental healthcare in New Zealand. From a survey of 227 older people, we explored the use of mental healthcare services with quantitative and qualitative questions. Mental health needs were not being met in nearly one in five; a similar proportion was not satisfied with services providing mental healthcare. Reasons included long waiting times, lack of continuity of care and cost. Better co-ordination of primary and secondary services and improved accessibility of mental health services for older adults is needed.